Is the vLamax for glycolysis what the VO2max is for oxidative phosphorylation? - Wackerhage, H.; Kabasakalis, A.; Seiler, S.; Heck, H. (Sports Medicine, 2025)
Oxidative phosphorylation and glycolysis are the two truly major energy metabolism pathways in humans. While maximal oxygen uptake (VO2max) has been used for a century as a whole-body measure of maximal oxidative phosphorylation, there is no universally accepted, comparable measure of maximal glycolysis. However, already in 1984, Alois Mader introduced the maximal rate of lactate accumulation in mmol/kg/s related to active muscle weight (vLamaxmuscle) for his mathematical model of human exercise metabolism. In 1994, on the basis of a critical analysis of glycolytic tests at the time, Mader proposed a practical test of the maximal rate of lactate accumulation in mmol per litre of earlobe or fingertip blood per second, corrected for alactic time (talac), that is measured during an ~ 10-15-s all-out exercise test (vLamaxblood). The variant vLamaxblood differs from the original vLamaxmuscle, as it is normalized to 1 L of blood volume and is today measured as the maximal rate of blood lactate accumulation in mmol/L/s. To measure it, participants typically perform a 10-15-s all-out test followed by quantification of the rise of the blood lactate concentration from pre-test to the maximum after exercise. Some few seconds of a 10-15-s all-out test are "alactic" and should be subtracted from the work time to more accurately estimate the vLamaxblood. However, (1) glycolytic flux is unlikely to be truly maximal during an all-out exercise test, (2) peak glycolytic flux occurs only briefly, (3) there is no criterion for reaching the vLamaxblood, (4) there is no correction for lactate clearance in the time from exercise cessation to blood sampling, (5) there is no correction for ATP resynthesis by oxidative phosphorylation and (6) the talac correction is error-prone. Therefore, we propose the peak rate of lactate accumulation in mmol/L/s in arterialized earlobe or fingertip blood during an all-out exercise test lasting 10-15 s (vLapeak) as a simplified estimate of peak glycolytic rate analogous to the VO2 peak. In contrast to the vLamaxblood, the vLapeak is not corrected for talac. Modelling using Alois Mader`s model of human exercise metabolism suggests that (with everything else being the same) a higher vLamaxmuscle will (a) improve performance in events where a large part of the hydrolysed ATP is resynthesized by glycolysis, (b) cause a leftward shift of the lactate curve and (c) increase carbohydrate usage and accelerate glycogen depletion at a given exercise intensity. There is large potential for research on the validation and improvement of vLapeak tests for athletes, healthy sedentary individuals and patients. This research should improve estimation of vLamaxmuscle from vLapeak and experimentally test the modelling predictions of the effects of changes in vLamaxmuscle on exercise performance and fatigue.